Impact Of Foreign Direct Investment On Economic Development In Algeria (2018-2022) - Merad Karima (جامعة الوادي University of Eloued, 2024)
Foreign Direct Investments (FDI) play a pivotal role in bolstering the economic capabilities of nations, particularlyin the context of globalization and the complex web of international economic interactions. FDIs act as vital channels for enhancing export capacities and introducing local products, equipped with advanced production technologies and contemporary management practices, into global markets through collaboration with multinational entities .This study delves into the dynamics of foreign direct investment in Algeria, scrutinizing the volume of incoming investments and illuminating the formidable challenges within the business and investment climate that undermine the efficacy of policies and assurances designed to attract capital and foreign investments. Furthermore, the analysis encompasses the principal characteristics and commitments extended by Algeria to encourage investment, along with their repercussions on economic progress.
Keywords: Foreign Direct Investment; investment flows in Algeria; barriers; economic development